Certainty Factor Method for an Expert System for Orthopedic Disease Diagnosis - Intan Savilla; Eva Rianti; Firna Yenila (Journal of Computer Scine and Information Technology, 2023)
Health is an important thing in human survival, including bone disease. Some people think that bones are passive, dead tissue, but they are not. Bones and skeleton are a very important part of orthopedics. Bones are not only a framework that strengthens the body but are also part of the structure of joints, as protection for the body, where the ends of muscles are attached. One of the diseases that is widely felt in society is bone disease. Bone disease is a condition that damages the skeleton and makes bones weak and susceptible to fractures. The high rate of diseases that attack the bones is caused by the conditions and behavior of society, such as stress, lack of exercise, wrong diet. Another cause is also ignorance and lack of knowledge about bone disease itself. By using an expert system, patients can save time going to the hospital, because the system replaces experts in their field, especially chiropractors. The method that will be used in this research is the Certainty Factor Method. The results obtained later are diagnostic results based on the symptoms entered and issued in the form of decisions and percentages. The diagnosis results identified Cervical Spondylosis (Nerve Pain) with a confidence level of 89.60%. It is hoped that this expert system will make it easier for patients to diagnose bone disease and carry out initial treatment in treating the disease.